PENGEMBANGAN MEDIA PEMBELAJARAN BONEKA TABLET UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA SISWA KELAS I SEKOLAH DASAR NEGERI 27 GERNIS - Evi Nur Islamiyati; Indri Astuti; Juhana Juhana (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to develop tablet puppet learning media to improve reading skills in first grade elementary school students. The research was conducted using the Research and Development method with the ADDIE development model through the analyze, design, development, implementation and evaluation stages. The research was conducted at 27 Gernis Public Elementary School in grade 1 with 70 participants. The tablet dummy media developed was validated by 2 material experts with an average score of 4.80 in the